Progress in Research on the Mechanisms and Interventions of Phlebitis from the Perspective of Vascular Endothelial Cell and Signaling Pathway - Zhu LL; Wang YH; Zhou Q (Dove Medical Press, 2023)
Ling-Ling Zhu,1 Yan-hong Wang,2 Quan Zhou2 1VIP Geriatric Ward, Division of Nursing, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 2Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaCorrespondence: Quan Zhou, Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, Zhejiang University, Jiefang Road No. 88, Hangzhou, Zhejiang Province, 310009, People's Republic of China, Email zhouquan142602@zju.edu.cnBackground: Phlebitis is a common complication of intravenous administration and greatly affects clinical outcomes, patient satisfaction, and health-care expenditure. Numerous studies have revealed venous injuries only through visual and histopathological examination. Although sporadic studies have explored the cellular and molecular biological mechanisms of phlebitis and the outcomes of pharmacological interventions, an updated review over the last decade is not available.Methods: Progress in research on the mechanisms and interventions of phlebitis was summarized from the perspective of endothelial cells and signaling pathways by retrieving the PubMed, Web of Science Core Collection, MEDLINE, Embase, and CNKI.Results: Phlebitis involves multiple signaling pathways (eg, nuclear factor kappa B, Wnt/β-catenin, focal adhesion kinase/protein kinase B, Toll-like receptor, protein kinase C beta/NADPH oxidase, PI3K/AKT/TNF, and JAK2/STAT3), upregulation of E-selectin, GBP5/NLRP3 inflammasome axis, cell apoptosis, intracellular ROS generation, SOD reduction, stimulation of angiogenesis, and induction of autophagy-associated cell death. Preventive and curative interventions included α-solanine, baicalein, escin, intermedin, Y15, micro-ribonucleic acid-223, sotrastaurin, cimetidine, aescin, resveratrol, α-chaconine, Chahuang ointment, QingLuoTongMai, Mailuo Shutong, and N-acetylcysteine. Laboratory models included vascular endothelial cells, real-time cell-monitoring analysis, network pharmacology analysis and experimental verification in vivo, animal models of phlebitis (rat, rabbit, and mouse), rabbit models with peripherally inserted central catheters (PICC) catheterization, models of PICC/central venous catheter indwelling with combined drugs in human umbilical vein endothelial cells, and compatibility with endothelial cells. Factors affecting vascular endothelial cell injury include difference in the same class of drugs, concentration and exposure time of precipitant, and infusion strategy.Conclusion: Phlebitis is accompanied by endothelial dysfunction and may involve multiple molecular and cellular mechanisms. These findings improve our understanding of the molecular targets of interventions and help identify effective candidates for the prophylaxis and treatment of phlebitis. Vascular health and risk management should be considered when initiating intravenous administration.Keywords: endothelial cells, intravenous infusion therapy, phlebitis, pharmacological interventions, peripherally inserted central catheters, signaling pathway